Pentingnya Pemerataan Pembangunan Ekonomi dalam Meningkatkan Kesejahtaraan Masyarakat Indonesia - Anggi Rizkina Sari Siregar; Namira Hamni Lubis; Fadhilla Isfa; Muzayyana Muzayyana (Pusat Riset dan Inovasi Nasional, 2025)
Equitable economic development in Indonesia is an important strategic issue to improve people's welfare. The purpose of this study is to examine how equitable development can reduce regional economic disparities and improve people's access to essential services including infrastructure, healthcare, and education. The research methodology was a qualitative approach with a literature review, which involved collecting and evaluating information from various academic sources and government records. The findings of this study show that equitable development enhances local economic growth and job creation in addition to improving living standards for populations in less developed areas. In addition, equitable development contributes to social and political stability, reduces conflict due to inequality, and strengthens national unity. This research provides recommendations for more effective and sustainable development equity policies, involving the active role of local governments and communities to achieve equitable and inclusive economic growth across Indonesia.